Identifikasi Wisata Alam Berbasis Kearifan Lokal Kelurahan Pahandut Seberang Kota Palangka Raya: Identification of Local Wisdom-based of Natural Tourism in Pahandut Seberang Village Palangka Raya City - Hamidah, Noor; Garib, Tatau Wijaya; Frieda, Frieda; Nuswantoro, Waluyo; Nindito, Dwi Anung; Santoso, Mahdi; Mahmudah, Noor (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
The Kahayan River is able to attract the attention of tourists and the people of Palangka Raya City through its natural potentials and portraits of community life on the riverside area. The Kahayan River has natural potential such as rivers, green open space, as a city buffer area, as well as cultural tourism, namely the uniqueness of settlements on the riverside area. The purpose of the service is to map the natural tourism potential of the Kahayan River area, Pahandut Seberang Village. The activity is located in Pahandut Seberang Village, Palangka Raya City. The method used is qualitative by describing descriptively and the stages of activities include: (a) preparation stage; (b) implementation stage; (c) post-implementation stage. The analysis and synthesis include descriptive elaboration of in-depth interview data with the community and village civil servant and the results of observational studies. The analysis applied to service activities include: (a) mapping analysis of the existing potential of the area, (b) mapping analysis of river tourism potential in Pahandut Seberang Village, (c) figure ground analysis of tourism potential in the Kahayan Riverside area, and (d) analysis of green open space tourism in Pahandut Seberang Village, Palangka Raya City. The output of this service activity provides a learning process for mapping the potential of natural tourism, analyzing the identification map of natural tourism, and analyzing the concept of nature tourism in Pahandut Seberang Village based on sustainable local wisdom.